Age and Gender Pattern of Dengue Disease in Lahore Epidemic of 2011 - MUHAMMAD SAEED ANWAR, GHAZALA JAFFERY, SHAHLA LATIF (Journal of Fatima Jinnah Medical University, 2018)
Objective: Gender and the age groups most affected by dengue fever were determined in patients coming to Services Hospital, Lahore during the 2011 epidemic for suspected dengue infection on clinical basis. This will help in the efficient allocation of health resources with reference to burden of Dengue Virus infection in local population. Study Design: An analytical study Place and Duration of Study: Microbiology Section, Department of Pathology, SIMS/Services Hospital, Lahore from November 2011 to December 2011. Methodology: Blood samples were received in a disposable properly labeled syringe. Sera were separated by centrifugation. Dengue NS1 antigen, Dengue IgM and Dengue IgG antibody ELISA tests were performed on these sera on the same day. Statistical evaluation of the results was performed by use of percentages and chi square test where applicable. Results: Two hundred and fifty samples of both gender were tested. Out of these 77.5% males and 65.5% female patients were positive for acute Dengue Virus infection with no significant difference between the two groups(>0.05). Age wise distribution of these cases revealed that positivity was significantly higher(<0.05) in age group less than 20 years (84.6%) as compared to age group more than 60 years(55%). Conclusion: Dengue Virus infection has occurred in children and adults more than the elderly. It has also been seen more in males than females. Hence, it is important to focus on cleansing of larva and mosquitoes from workplaces, schools and colleges. There is need for regular monitoring of this problem with measures to control the vector responsible for this problem.